Large-area semi-transparent light-sensitive nanocrystal skins - Akhavan, Shahab (2013)
We report a large-area, semi-transparent, light-sensitive nanocrystal skin (LS-NS) platform consisting of single monolayer colloidal nanocrystals. LS-NS devices, which were fabricated over areas up to 48 cm2 using spray-coating and several cm-squares using dip-coating, are operated on the principle of photogenerated potential buildup, unlike the conventional charge collection. Implementing proof-of-concept devices using CdTe nanocrystals with ligand removal, we observed a substantial sensitivity enhancement factor of ~73%, accompanied with a 3-fold faster response time (<100 ms). With fully sealed nanocrystal monolayers, LS-NS is found to be highly stable under ambient conditions, promising for low-cost large-area UV/visible sensing in windows and facades of smart buildings.